SAPI PERAH: MASALAH DAN SOLUSI PENINGKATAN PRODUKSI SUSU (KASUS DI KELOMPOK TANI SEPAKAT II, DESA MOJOREJO, KABUPATEN REJANG LEBONG) - Zul Efendi; Andi Ishak; Wahyuni A Wulandari; Afrizon Afrizon (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
This research was conducted in April to August 2019 at the Sepakat II Livestock Group, Mojorejo Village, Sindang Kelingi District, Rejang Lebong District. The purpose of this research is to analyze the problems and solutions to increase milk production in dairy cows in the Sepakat II farmer group in Mojorejo Village, Sindang Kelingi District, Rejang Lebong Regency. Data collected in the form of technical, economic and management data for dairy cattle maintenance. Technical and economic data, i.e. types, sources, nutrition, and feed costs. Data about the type and source of feed were obtained by means of individual interviews and FGDs. Nutrient content was obtained through laboratory analysis at the University of Bengkulu Animal Husbandry Laboratory. Feed management data is in the form of problem analysis and problem solving solutions collected through individual interviews. Data were analyzed descriptively and using problem tree analysis and AHP (Analitycal Hierarchy Process). The results obtained that the priority of technological innovation in the context of increasing milk production in dairy cows in the Sepakat II Farmers Group are the utilization of location-specific alternative concentrates (63.7%), superior grass planting (25.8%) and extension technology for dairy farming (10, 5%). Keywords: Problems, Solutions, Increase, Milk Production, Dairy Cows.